Differential effects of cathodal transcranial direct current stimulation of prefrontal, motor and somatosensory cortices on cortical excitability and pain perception – a double‐blind randomised sham‐controlled study. (12th September 2015) - Vaseghi, B.; Zoghi, M.; Jaberzadeh, S.; Thut, Gregor
Abstract The primary aim of this study was to assess the effects of cathodal transcranial direct current stimulation (c‐tDCS) over cortical regions of the pain neuromatrix, including the primary motor (M1), sensory (S1) and dorsolateral prefrontal (DLPFC) cortices on M1/S1 excitability, sensory (STh), and pain thresholds (PTh) in healthy adults. The secondary aim was to evaluate the placebo effects of c‐tDCS on induced cortical and behavioural changes. Before, immediately after and 30 min after c‐tDCS the amplitude of N20–P25 components of somatosensory evoked potentials (SEPs) and peak‐to‐peak amplitudes of motor evoked potentials (MEPs) were measured under four different experimental conditions. STh and PTh for peripheral electrical and mechanical stimulation were also evaluated. c‐tDCS of 0.3 mA was applied for 20 min. A blinded assessor evaluated all outcome measures. c‐tDCS of M1, S1 and DLPFC significantly decreased the corticospinal excitability of M1 (P < 0.05) for at least 30 min. Following the application of c‐tDCS over S1, M1 and DLPFC, the amplitude of the N20–P25 component of SEPs decreased for at least 30 min (P < 0.05). Compared with baseline values, significant STh and PTh increases were observed after c‐tDCS of these three sites. Decreasing the level of S1 and M1 excitability, following S1, M1 and DLPFC stimulation, confirmed the functional connectivities between these cortical sites involved in pain processing. Furthermore, increasing the level of STh/PTh after c‐tDCS of these sites indicated that stimulation of not only M1 but also S1 and DLPFC could be considered a technique to decrease the level of pain in patients.